Telepresence in Ecuador - Schoonover, Hannah; Thomas, Mia (My University, 2023)
The Telepresence in Ecuador project served to analyze and gain an understanding of virtual education with an emphasis in building relationships with students and English language acquisition. The project was completed through a partnership with Kansas State University and ULEAM in Manta, Ecuador. An honors section of Educational Technology (EDCI 318) took on the project, using Double 2 robots to access the Ecuadorian classrooms. The K-State students in the class were split into pairs and assigned a school. The K-State students focused on improving the English pronunciation and vocabulary of the Ecuadorian students through the use of literature circles, games, and conversation. The project found that conversation with the students not only helped to improve their pronunciation as they listened to native English speakers, but it also rapidly built relationships and trust with the students. This project focuses on the qualitative experiences of the authors rather than the quantitative data, as the project was still in its early stages when the authors were involved. https://youtu.be/QRrAnActlsI